PENGARUH KEPEMIMPINAN, MOTIVASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN (Studi Pada KPRI BHAKTI PRAJA Semarang) - Putri Ratnasari Dewi, 14.05.51.0106; Kasmari, Kasmari (Students' Journal of Economic and Management, 2018)
This study aims to analyze the Effect of Leadership, Motivation and Competence Tehadap Employee Performance KPRI Bhakti Praja Semarang.The population in this study is the total number of employees, amounting to 52 respondents. The data used is the primary data, the data obtained directly from the source. Data collection techniques were conducted with questionnaires. The method of analysis used is data feasibility test, model feasibility test, test using multiple linear regression.The research result proves that the ability of model in explaining correctly influence of leadership, motivation and competence is 97,7% to employee performance. While the other by 02.3% influenced by other variables. Keywords: Leadership, Motivation, Competence and employee performance